"Effect of nano-filled surface coating agent on fluoride release from conventional glass ionomer cement: An in vitro trial" - S Tiwari; B Nandlal (Wolters Kluwer Medknow Publications, 2013)
Context: To overcome the drawbacks of glass ionomer cement of sensitivity to initial desiccation and moisture contamination the use of surface coating agent is recommended. The search in this area led to invent of use of nanofillers in surface coating agent, but its effect on fluoride release is not clear. Aim: The aim of this study is to evaluate and compare the fluoride release from conventional glass ionomer cement with and without surface coating agent. Settings and Design: This in vitro study comprised of total 80 samples (40 samples of each with and without surface coating). Materials and Methods: Specimens were prepared, G coat plus was applied and light cured. Fluoride release of the sample was measured every 24 h for 7 days and weekly from 7th to 21 st day using Sension4 pH/ISE/MV Meter. Statistical Analysis Used: Descriptive Statistics, Repeated Measure ANOVA, Paired Sample t-test, Independent Sample t-test, Scheffe post hoc test. Results: Mean values clearly reveal a significant decrease in the fluoride release from day 1 to day 21 for both groups. Non-coated group released significantly more fluoride than surface coated group (P < 0.001). Conclusions: It can be concluded that nanofilled surface coating agent will reduce the amount of fluoride released into oral environment as compared to non-coated group and at the same time releasing fluoride into surrounding cavity walls to create zones of inhibition into the cavity floor to help internal remineralization.